Modeling hearing tests in Syria during the period (2018 – 2022) (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The research aimed to shed light on the reality of hearing tests in Syria and the changes that occurred during the period (2018 -2022) .The descriptive analytical approach based on analyzing the research series to hearing tests which is a year series starting from 2018 and it ends in 2022 were taken from the Syrian statistical collection .The study reached several results, the most important of which are:• that the monthly series of hearing tests is stable at the first difference.• The ARIMA (0, 1,1) model the model which consider good to modeling hearing tests